Specific Deletion of the Astrocyte Leptin Receptor Induces Changes in Hippocampus Glutamate Metabolism, Synaptic Transmission and Plasticity. (1st November 2020) - Naranjo, Víctor; Contreras, Ana; Merino, Beatriz; Plaza, Adrián; Lorenzo, María P.; García-Cáceres, Cristina; García, Antonia; Chowen, Julie A.; Ruiz-Gayo, Mariano; Del Olmo, Nuria; Cano, Victoria
Highlights: Astrocyte LepR deletion reduces basal synaptic transmission in the hippocampus. Astrocyte LepR modulate NMDA-induced LTD within the hippocampus. Astrocyte LepR regulate the expression of the glutamate transporter GLT-1. Astrocyte LepR are involved in glutamate uptake and neurotransmission. Abstract: The aim of this study was to indentify the involvement of leptin receptors (LepR) in astrocytes in hippocampal synaptic transmission and plasticity and metabolism. To this end we used a genetic mouse model (GFAP-LepR −/− ) of specific LepR ablation in GFAP positive cells and recorded excitatory postsynaptic potentials (fEPSPs) within the CA1 area. Glutamate (Glu) uptake and the expression of Glu transporters (EEAT3, GLT-1 and GLAST) and enzymes involved in Glu metabolism (glutamine synthase, GABA decarboxylase 65 and 67) were quantified. Modifications in the expression of GFAP, the glucose transporter (GLUT)-1, and the monocarboxylate transporters MCT-2 and MCT-4, were also analyzed. The results show that depletion of LepR in GFAP positive cells reduced basal synaptic transmission within the CA1 area and impaired N -methyl-d -aspartate (NMDA)-evoked long-term depression (NMDA-LTD). Hippocampal slices from GFAP-LepR −/− mice displayed lower Glu uptake efficacy together with up-regulation of GLT-1, glutamine synthase, GFAP and GLUT-1. In conclusion, astrocyte LepRs are involved in the maintenance of Glu homeostasis and Glu neurotransmission within the hippocampus. Our findings support a role of hippocampal LepRs in synaptic plasticity, which could have an impact on memory and learning processes.